Elevated plasma total homocysteine levels are associated with behavioral and psychological symptoms in dementia with Lewy bodies - Zhang, Guili; Liu, Shuai; Xu, Ying; Ma, Ling-Yun; Zhang, Wei; Ji, Yong (Frontiers in Neuroscience, 2024)
ObjectiveTo investigate the association between plasma total homocysteine (tHcy) levels and behavioral and psychological symptoms of dementia (BPSD) in dementia with Lewy bodies (DLB) patients.MethodsA total of 82 DLB patients and 134 age-matched healthy controls were included in this study. DLB patients were assessed using the Mini-Mental Status Examination (MMSE), the Clinical Dementia Rating Scale (CDR), and the Neuropsychiatric Inventory (NPI). Plasma tHcy, serum vitamin B12, and folate levels were measured in all study participants. We used Spearman’s rank correlation test to analyze the association between tHcy concentrations and NPI scores, MMSE, CDR, and the duration of dementia in DLB patients.ResultsClinically significant BPSD was present in 92.7% of DLB patients. The most frequent BPSD were hallucinations (30.4%), apathy (30.4%), and delusions (26.8%). Elevated plasma tHcy levels were significantly associated with total NPI scores in DLB patients, particularly in 10 NPI sub-domains, except for agitation/aggression and disinhibition. No statistically significant association was found between plasma tHcy levels and MMSE, CDR, or dementia duration.LimitationsLongitudinal studies with larger sample sizes are required to further explore the relationship between tHcy levels and BPSD in DLB patients as the disease progresses.ConclusionOur study highlighted the high incidence of BPSD and was the first to show that BPSD is associated with elevated plasma tHcy levels in DLB patients in China. These results support the hypothesis that controlling homocysteine levels could offer a new direction for managing BPSD.